Randomized adaptive assessment of post COVID syndrome treatments (RAPID): a study protocol for a multicenter, randomized, controlled adaptive platform trial of treatment options for Post Covid Syndrome (PCS) on patients physical function including the first intervention specific appendix RAPID_REVIVE (reducing inflammatory activity in patients with PCS) - Lisa Weipert; Ralph G. Telgmann; Gabriele Anton; Thomas Asendorf; Irina Chaplinskaja-Sobol; Sandra Ciesek; Oliver A. Cornely; Sonja Drescher; Carsten Finke; Tim Friede; Julia Groth; Sabine Hanß; et al. (Trials)
Abstract Background The majority of patients recovers from severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) coronavirus disease 2019 (COVID-19) without obvious sequelae, but a significant proportion suffers long-term consequences which have been termed post COVID syndrome (PCS). Despite a wide range of considerations on treatment options in PCS and a significant number of trials initiated, only very few results from randomized controlled trials are currently available. In conclusion, there is an evident medical need to identify treatments for patients with PCS. Methods The primary objective of the platform trial RAPID is to assess the impact of different PCS treatments on the overall physical function of patients. Designed as a master protocol, RAPID contains all information that is generic to this adaptive platform trial. Current and future study treatments are specified in intervention-specific appendices (ISA). The first ISA, RAPID_REVIVE is presented in this manuscript. General sections of the master protocol are named as such. RAPID_REVIVE is a double-blind, placebo-controlled, phase II clinical trial evaluating antiviral PCS treatment with vidofludimus calcium (IMU-838). Patients are randomized at a 1:1 ratio to 45 mg/day vidofludimus calcium (22.5 mg for the first 7 days) or placebo during an initialization phase and thereafter using a response-adaptive randomization procedure. The trial includes a screening period of 7 days, a double-blind treatment period of 56 days and a follow-up period of 28 days. The primary outcome is the intra-patient change in physical function measured by the Short Form-36 Physical Function (SF-36-PF) from baseline to day 56. Secondary endpoints include mental and physical health, intensity of fatigue, severity of mental disorder symptoms, and cognitive function. Discussion PCS is a major problem for global health care and the identification of treatment options is urgently needed. Currently, PCS patients are in a situation without evidence-based treatment options, and quality of life, and often mental health are significantly impaired. The purpose of RAPID is to establish an adaptive platform trial protocol which will concert and quicken clinical trials to evaluate the efficacy and safety of different potential treatments for PCS with the aim to expand the very limited evidence base for the treatment of PCS. Trial registration EU Clinical Trials Register (CTIS) ID: 2024–511628-16–00 (RAPID_REVIVE). Registered on 18.03.2024.